The first successful endoscopic atraumatic coronary artery bypass graft for coronary artery disease in Slovenia: Prva uspešna endoskopska kirurška revaskularizacija miokarda pri ishemični bolezni srca v Sloveniji - Djordjević, Anže; Robič, Boris; Jurič, Peter; Petrovič, Rene; Železnik, Jernej; Antonič, Miha (Acta Medico-Biotechnica, 2022)
Purpose: oronary artery bypass graft (CABG) using median sternotomy remains the standard care for patients with multi-vessel coronary artery disease (CAD). However, median sternotomy considerably affects morbidity and mortality after cardiac surgery. For this reason, less invasive access routes, including mini–thoracotomy or mini–sternotomy, have been developed to avoid full median sternotomy.Case report: A 42–year–old male patient with a single–vessel CAD was admitted to the Department of Cardiac Surgery, University Medical Centre Maribor for surgical treatment. Endoscopic mammary artery harvesting and direct left internal mammary artery to left anterior descending artery anastomosis via left mini–thoracotomy were performed. The early postoperative course was uneventful and the patient was discharged on the fifth postoperative day.Conclusion: This report presents the first case of a minimally invasive CABG procedure using endoscopic mammary artery harvesting in Slovenia.
Keywords: cardiac surgery, cardiopulmonary bypass, coronary artery bypass, minimally invasive surgery